2014
DOI: 10.1021/ic500822w
|View full text |Cite
|
Sign up to set email alerts
|

Cu3I7 Trimer and Cu4I8 Tetramer Based Cuprous Iodide Polymorphs for Efficient Photocatalysis and Luminescent Sensing: Unveiling Possible Hierarchical Assembly Mechanism

Abstract: Solvothermal reactions of CuI, 1,4-diazabicyclo[2.2.2]octane (DABCO), and HI in an ethanol solution at 140 °C/150 °C for 7 days resulted in two 24-membered-ring-based layered semiconducting iodocuprate open-network polymorphs formulated as [deDABCO]2[meDABCO]Cu11I17 (deDABCO = N,N'-diethyl-1,4-diazabicyclo[2.2.2] octane and meDABCO = N-methyl-N'-ethyl-1,4-diazabicyclo[2.2.2]octane). The deDABCO and meDABCO templates were in situ generated via alkylation of DABCO during solvothermal reactions. The formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…The rising Eg with 1 may be in part ascribed to significant deviation of TPPB ligands from quasi-planar conformation, which disrupts the π-conjugation. Copper(I) iodide has been used to construct coordination polymers with conductive properties owing to its intrinsic semiconductive nature [16][17][18][19]. However, it was found that {[(TEPB) Cu 2 I 2 ]·CH 3 CN} n behaves as an insulator.…”
Section: Uv-vis Spectroscopic and Conductive Properties Ofmentioning
confidence: 99%
“…The rising Eg with 1 may be in part ascribed to significant deviation of TPPB ligands from quasi-planar conformation, which disrupts the π-conjugation. Copper(I) iodide has been used to construct coordination polymers with conductive properties owing to its intrinsic semiconductive nature [16][17][18][19]. However, it was found that {[(TEPB) Cu 2 I 2 ]·CH 3 CN} n behaves as an insulator.…”
Section: Uv-vis Spectroscopic and Conductive Properties Ofmentioning
confidence: 99%
“…With the coordination flexibility and luminescent properties of Cu(I) complex, coordination polymers constructed with CuI aggregates possess significant structural diversity and unique physical properties. For example, they have been previously investigated for their excellent photoluminescent properties [42][43][44][45][46][47] , potential as photocatalysts 48,49 , and as hole-transporting materials in perovskite solar cells 50 . With different bridging organic ligands, various CuI architectures, such as rhombus dimer connectors, zig-zag chains and staircase chains, have been constructed, which extend the crystal engineering of Cu(I) halides from discrete oligomers to coordination polymers with one, two and three-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…11 The first subgroup contains the most explored neutral compounds, in which both the inorganic motif (CuxXx) and organic ligand (L) are charge neutral and connected via Cu-L coordinate/dative bonds; [18][19][20][21]23 the second subgroup is the pure ionic compounds, formed by co-crystallization of anionic inorganic and cationic organic motifs but without coordinate bonds between these building blocks. [24][25][26][27][28] Ionic ligands have also been used in forming anionic MOFs and show interesting structural directing effects. 29 Recently, we have developed a brand new subgroup using ligands deliberately designed to have both cationic centers (quaternary N or P atoms) and coordination-active sites toward Cu(I) atoms.…”
Section: Introductionmentioning
confidence: 99%